Case report: Escitalopram-associated lower limb edema - Ahmed, Mohamed Hassan; Al-Kubaisi, Mena; Al-Rawi, Safa Abdulmajeed; Salama, Omar Hosam; Abutayyem, Hebah Mahmoud (Frontiers in Psychiatry, 2024)
Escitalopram is widely prescribed for the treatment of major depressive disorder and generalized anxiety disorder with a well-documented side effects profile. Peripheral edema, however, is a rarely reported adverse reaction that warrants further work up. This paper summarizes the case of a 58-year female patient who developed transient bilateral peripheral edema following the administration of low dose escitalopram. This case underscores the necessity for clinicians to be familiar with even rare potential side effects of commonly prescribed medications. It also suggests a need for patient education regarding the importance of reporting new symptoms promptly.